Accumulation of Heavy Metals in Soil and Cultivated Crops - Kurganbekov, Zhangeldi N.; Utebayev, Aspondiyar A.; Domatskiy, Vladimir N.; SMukataeva, Zhazira; Zhetpisbay, Dinara Sh. (Journal of Environmental Accounting and Management, 2026)
A modern understanding of crop growth productivity allows us to expand our ecological culture using the land fund. However, the impact of industrial enterprises determines the structural content and increase of soil pollution level. The relevance of this study is determined by the fact that the formation of measures that would contribute to reducing soil pollution is currently based not only on the economic assessment of measures, but also on reducing the allowable impact on environmental metabolism and maintaining balance in the circulation of substances. The novelty of the study is determined by the need to develop a model that takes into account the capabilities of modern biological agents to form complex chemical complexes that can reduce the concentration of heavy metals. The authors propose a model that can provide a solution to the problems of the separation of heavy metals with the formation of a complex of a biologically utilizable type. The authors determine the accumulation complexes, their chemical composition and, if necessary, the reagents used. The practical significance of the study is formed due to the strategic development of the chemical complex. In this vein, considered the possibility of using chemical compounds that can be used as producers for the formation of a new fertile layer after the accumulation of heavy metals in the skeletal structure of plants.